2020
DOI: 10.1371/journal.pone.0235490
|View full text |Cite
|
Sign up to set email alerts
|

KRAS, NRAS, and BRAF mutation prevalence, clinicopathological association, and their application in a predictive model in Mexican patients with metastatic colorectal cancer: A retrospective cohort study

Abstract: Mutations in KRAS, NRAS, and BRAF (RAS/BRAF) genes are the main predictive biomarkers for the response to anti-EGFR monoclonal antibodies (MAbs) targeted therapy in metastatic colorectal cancer (mCRC). This retrospective study aimed to report the mutational status prevalence of these genes, explore their possible associations with clinicopathological features, and build and validate a predictive model. To achieve these objectives, 500 mCRC Mexican patients were screened for clinically relevant mutations in RAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
4
17
3
Order By: Relevance
“…The median age of onset of the disease in the included patients was 63.5 years, which corresponds to the data from other populations [23][24][25][26]. The majority (61.7%) of the patients were aged over 60 years, and only 2 (5.9%) patients were younger than 45 years old (Table 2).…”
Section: Discussionsupporting
confidence: 79%
“…The median age of onset of the disease in the included patients was 63.5 years, which corresponds to the data from other populations [23][24][25][26]. The majority (61.7%) of the patients were aged over 60 years, and only 2 (5.9%) patients were younger than 45 years old (Table 2).…”
Section: Discussionsupporting
confidence: 79%
“…KRAS mutations occurred significantly more frequently in African Americans than Caucasians (37% vs. 21%, P = 0.01) and were associated with worse stage or grade of CRC [28] . It is noteworthy that such a difference is mainly caused by codon 12 mutations: indeed, many studies have reported that codon 12 mutations are significantly more frequent in African Americans than Caucasians (P = 0.04), whereas the frequencies of mutations in codon 13, exon 3, and exon 4 did not differ significantly according to ethnicity [27][28][29] . Interestingly, even within the same ethnic group, there can be differences.…”
Section: Kras Differences In the Heterogeneous American Populationmentioning
confidence: 97%
“…It has been presented that NRAS mutations are rare CRCs and do not appear to be associated with any of the molecular features, including mutation of KRAS , BRAF , PIK3CA , MSI, and CIMP [ 44 ]. Moreover, the frequency of double mutations involving NRAS mutations is rare [ 45 , 46 ]. Only three samples displayed triple mutations from the cases studied here (n = 2347), including NRAS , and analysis was impossible.…”
Section: Discussionmentioning
confidence: 99%